A study of the effects of plane of nutrition on milk secretion and lamb growth in Romney sheep, and the effect of weaning date on the growth of Romney lambs : a thesis presented in partial fulfilment of the requirements for the degree Master of Agricultural Science of the University of New Zealand - Murray, Paul Frederick (Massey University, 1952)
The productivity of an animal depends on two factors, its potentiality, which is governed by its hereditary make-up, and the extent to which that potentiality is allowed to develop, this being regulated by the environment that characterises the habitat. The effects of genotype are obviously shown by the differences between breeds of stock in the amount and quality of meat, wool and milk they produce; but within breeds these effects are not so apparent though they have been conclusively demonstrated, e.g. yield and quality between flocks of Romney sheep. Environmental influence on productivity is limited at the maximum level by the genotype, i.e. no matter how good the environment, the animal cannot produce more than the maximum ordained by the genes it possesses. Conversely, below the genotypic maximum, the environment can regulate the coiling level of production. This interplay of factors is well illustrated by the adaptability of different breeds of sheep to different habitats, e, g. the Romney is predominant in the North Island hill country while in the South the Merino and its crosses assume a greater importance. Within a population with approximately common genotype, e.g. a single flock of uniform breed, the effects of environment below the threshold set by the genotype can be widely varied, e.g. the growth of lambs in a drought can be severely set back. It is with the effects of a particular factor of environment, i.e. nutrition, on the milk production and lamb growth of such a population that this investigation is concerned.
Keywords: Sheep; Romney Marsh sheep; Nutrition; Breeding